On the Trail of the Oldest Domestic Cat in Poland. An Insight from Morphometry, Ancient DNA and Radiocarbon Dating. (September 2016) - Krajcarz, M.; Makowiecki, D.; Krajcarz, M. T.; Masłowska, A.; Baca, M.; Panagiotopoulou, H.; Romańska, A.; Bednarczyk, J.; Gręzak, A.; Sudoł, M.
Abstract: It is believed on the basis of archaeozoological research that the domestic cat appeared in Central Europe during the Roman Period. In Poland, the domestic cat is a common species in medieval deposits. Only a few finds of cat remains of pre‐medieval age have been reported from Poland to date, including several specimens from deposits older than the Roman Period, dated to the pre‐Roman Period and even the Bronze Age. To clarify the earliest history of the domestic cat in Poland, the paper presents a review of the available published cat remains and adds some data about newly discovered remains. Combined methods of morphometry and ancient DNA were applied to enable distinction of wildcats and domestic cats. The domestic cat remains were radiocarbon dated. In six cases of domesticated cat reported in the literature, five were positively taxonomically verified, both by morphology and by genetic analysis, and one was recognised as a European wildcat. According to radiocarbon chronology, the oldest studied find is dated to the fourth–third centurybc and represents a wildcat. Only two individuals of domestic cat – skeletons from Łojewo and Sławsko Wielkie, both from Kuyavia region (central‐northern Poland) – represent the Roman Period (first–third centuryad ), and they are the oldest confirmed domestic cats in Poland. Copyright © 2015 John Wiley & Sons, Ltd.